Mapping the Thermal Structure of Southern Africa From Curie Depth Estimates Based on Wavelet Analysis of Magnetic Data With Uncertainties - M. Sobh; C. Gerhards; I. Fadel; H.‐J. Götze (Geochemistry, Geophysics, Geosystems, 2021)
Abstract Surface heat flow provides essential information on the thermal state and thickness of the lithosphere. Southern Africa is a mosaic of the best‐preserved and exposed crustal blocks, assembled in the early late Archean and then modified by a series of major tectono‐thermal events, both of Precambrian and Phanerozoic. Understanding the thermal and compositional structure of the southern African lithosphere provides crucial information for the actual causes, processes of lithospheric stability, and modification. Curie depth, interpreted as the depth to 580°C, provides a valuable constraint on the thermal structure of the lithosphere. Due to the sparse distribution of surface heat flow data, we examine the degree to which the thermal structure of the crust can be constrained from Curie depth estimates in southern Africa. We provide a Curie depth map for southern Africa (obtained from the inversion of magnetic anomaly data via power spectral methods and wavelet analysis) alongside with a heat flow map (based on the previous Curie depth estimates), both equipped with uncertainties via a Bayesian approach. Opposed to other cratonic regions, the observation of a shallow Curie depths and low heat flow over the Kaapvaal Craton suggests a thermochemical reworking of the cratonic lithosphere in this region. Furthermore, a comparison with a model for the Moho depth reveals significant variations of the Curie depth, which may be located below or above the Moho in large regions. Both observations indicate that in certain regions magnetic anomaly based Curie depth estimates may reflect a compositional rather than a temperature controlled constraint.